AUDIT OF COVID-19 WARD PERFORMANCE AND PRACTICE IN THE COVID-19 PANDEMIC: FUTURE DIRECTIONS FOR UNDERSTANDING: A RETROSPECTIVE STUDY - AFRIDI , F; GHAYAS , F; ANWAR , S; SHEIKH , MA (Biological and Clinical Sciences Research Journal, 2024)
A retrospective study was conducted to assess the trend of the COVID-19 pandemic in the COVID Ward emergency and COVID Ward treatment departments of the Department of COVID Ward at POF Hospital Wah Cantt from January 2021 to January 2022. Data on every patient admitted to the COVID Ward department over a year was gathered retroactively. The following demographic factors were recorded: diagnosis, COVID-19 work-up, admission specialization, and COVID-19 ward vs. conservative therapy. In total, there were 156 patients, with 108 being primarily men (70.4%). Of these patients, 90 (72%) were admitted via the clinic, and 124 (46%) were admitted in May. One hundred five patients (62.8%) had a COVID-19 PCR, 135 had a chest x-ray (90.2%), and 56 patients (31.4%) had a chest HRCT. The orthopedic COVID Ward was the most common department for operational interventions, with 88.4% of patients undergoing operative care, despite the general COVID Ward being the busiest service line with 89 total patient admissions (43.1%). The study found that the existing local protocols for patient flow and COVID-19 crisis management are effective and practical. Hospitals should be prepared to redirect their resources to high-volume specialties like orthopaedics and general COVID Wards after the later COVID-19 waves. Arteriovenous fistula formation is a simple yet crucial technique that should only be discontinued in the event of a labor shortage.